Congruence constructs as mediators of stereotypic image perceptions' effect on student volunteering intention - Jörg Lindenmeier; Christian Arnold; Adnan Zogaj; Dieter K. Tscheulin (International Review on Public and Nonprofit Marketing, 2021)
This study aims to analyze the effects of ideal and actual self-congruence and functional congruence on the volunteering intentions of university students. The empirical analysis is based on a sample of 735 students from universities in southwestern Germany. The current paper shows that stereotypic image perceptions (i.e., perceived warmth and competence) represent antecedents of the considered congruence constructs. Moreover, the study shows that actual self-congruence and functional congruence mediate the effect of perceived warmth and competence on the intention to volunteer. Ideal self-congruence did not mediate the effect of stereotypical image perceptions, nor did it have a direct effect on the willingness to take voluntary action. The study offers practical recommendations for nonprofit organizations, as well as avenues for future research based on its empirical findings.
Keywords: 380; Self-congruity; Volunteering; Germany; Stereotypes